Greenhouse gas emission and exergy analyses of an integrated trigeneration system driven by a solid oxide fuel cell. (5th July 2015) - Chitsaz, Ata; S. Mahmoudi, S. Mohammad; Rosen, Marc A.
Abstract: Exergy and greenhouse gas emission analyses are performed for a novel trigeneration system driven by a solid oxide fuel cell (SOFC). The trigeneration system also consists of a generator-absorber heat exchanger (GAX) absorption refrigeration system and a heat exchanger to produce electrical energy, cooling and heating, respectively. Four operating cases are considered: electrical power generation, electrical power and cooling cogeneration, electrical power and heating cogeneration, and trigeneration. Attention is paid to numerous system and environmental performance parameters, namely, exergy efficiency, exergy destruction rate, and greenhouse gas emissions. A maximum enhancement of 46% is achieved in the exergy efficiency when the SOFC is used as the primary mover for the trigeneration system compared to the case when the SOFC is used as a standalone unit. The main sources of irreversibility are observed to be the air heat exchanger, the SOFC and the afterburner. The unit CO2 emission (in kg/MWh) is considerably higher for the case in which only electrical power is generated. This parameter is reduced by half when the system is operates in a trigeneration mode. Highlights: A novel trigeneration system driven by a solid oxide fuel cell is analyzed. Exergy and greenhouse gas emission analyses are performed. Four special cases are considered. An enhancement of up to 46% is achieved in exergy efficiency. The CO2 emission drops to a relatively low value for the tri-generation case.